1996
DOI: 10.1128/mcb.16.12.6661
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of RNA Hairpins Mediated by a Developmentally Regulated CCCH Zinc Finger Protein

Abstract: Control of RNA turnover is a major, but poorly understood, aspect of gene regulation. In multicellular organisms, progress toward dissecting RNA turnover pathways has been made by defining some cis-acting sequences that function as either regulatory or cleavage targets (J. G. Belasco and G. Brawerman, Control of Messenger RNA Stability, 1993). However, the identification of genes encoding proteins that regulate or cleave target RNAs has been elusive (C. A. Beelman and R. Parker, Cell 81:79-183, 1995); this gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 27 publications
2
74
0
Order By: Relevance
“…Clipper contains five CCCH zinc finger motifs and two zinc knuckle motifs, and the high sequence conservation covers the five zinc finger motifs. This region of clipper has endoribonuclease activity and cleaves RNA hairpins [130]. Consequently, it has been suggested that CPSF-30 might be the endoribonuclease responsible for the cleavage reaction [131].…”
Section: Cpsf-30 (Yth1p)mentioning
confidence: 99%
“…Clipper contains five CCCH zinc finger motifs and two zinc knuckle motifs, and the high sequence conservation covers the five zinc finger motifs. This region of clipper has endoribonuclease activity and cleaves RNA hairpins [130]. Consequently, it has been suggested that CPSF-30 might be the endoribonuclease responsible for the cleavage reaction [131].…”
Section: Cpsf-30 (Yth1p)mentioning
confidence: 99%
“…This domain is found in a subset of zinc-finger family proteins; its consensus sequence corresponds to C-X 8-10 -C-X 5 -C-X 3 -H, where X refers to any amino acid (Varnum et al 1989). CCCH zinc fingers were first described in the mouse TIS11 protein, where they are responsible for nucleic-acid binding (Varnum et al 1989;DuBois et al 1990;Bai and Tolias 1996). Mammalian TIS11-like zinc-finger-containing proteins have been shown to function either as transcription factors or RNA-binding proteins (Taylor et al 1996;Worthington et al 2002).…”
Section: Identification Of Mutations In the C Elegans Gla-3 Genementioning
confidence: 99%
“…The goal of our study was to investigate the potential of the salt stress tolerant candidate gene in major crop such as soybean. Among many candidate genes, CCCH-type zinc finger protein which has shown to be associated with RNA metabolism (Bai and Tolias 1996;Carballo et al 1998;Lai et al 2006;Hurt et al 2009) and known to be involved in abiotic and biotic stresses could be a good gene source for salt stress tolerance. In previous report, GHZFP1, a CCCH-type zinc finger protein from cotton, was found to enhance the tolerance of salt stress ).…”
Section: Discussionmentioning
confidence: 99%
“…CCCH-type zinc finger proteins role as DNA-binding transcription factors. However, most of CCCH-type zinc finger proteins have shown to be associated with RNA metabolism by directly binding to RNA targets (Bai and Tolias 1996;Carballo et al 1998;Lai et al 2006;Hurt et al 2009). In addition, some CCCH zinc finger proteins are involved in abiotic and biotic stresses.…”
Section: Introductionmentioning
confidence: 99%